Simulated Learning in STEM Education: Bridging Theory and Practice Through AR - Titik Haryanti; Dina Destari; Noura Rizqyaannisa Hidayat; Agung Yuliyanto Nugroho; Achmad Nashrul Waahib (Journal Emerging Technologies in Education, 2024)
Background. The integration of augmented reality (AR) into STEM education has gained attention for its potential to bridge the gap between theoretical knowledge and practical application. Traditional methods of teaching STEM subjects often struggle to provide students with immersive, hands-on learning experiences, which are crucial for understanding complex concepts. AR, with its ability to create simulated environments, offers a solution by making abstract theories more tangible and interactive. However, the impact of AR-based simulated learning on student outcomes remains underexplored. Purpose. This study aims to investigate the effectiveness of AR in enhancing STEM education by simulating real-world applications of theoretical concepts. Method. The research utilized a mixed-method approach, combining quantitative assessments of student performance and qualitative feedback from students and educators. A sample of 300 high school students participated, using AR-enhanced learning modules in subjects like physics, chemistry, and biology. Data were collected over a semester, focusing on improvements in comprehension, engagement, and practical application of STEM knowledge. Results. The results showed a significant improvement in students' understanding of STEM concepts, with a 28% increase in test scores compared to traditional learning methods. Student engagement levels were also higher, as AR provided interactive, visually rich learning experiences. Educators reported that AR helped students connect abstract theories to real-world applications, fostering a deeper understanding of STEM subjects. Conclusion. In conclusion, the study demonstrates that AR-based simulated learning is an effective tool for enhancing comprehension and engagement in STEM education. These findings suggest that AR has the potential to transform how STEM subjects are taught, making learning more immersive and applicable to real-life contexts.